Review Artikel: Sitotoksisitas Ekstrak Etanol Tumbuhan Mengkudu (Morinda Citrifolia L) Terhadap Sel Kanker - Haryoto Haryoto; Gita Firdaus (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Cancer is a disease that can attack any part of the body when the abnormal cells begin to grow uncontrollably beyond the limit, then attack the connected parts of the body and / or spread to other organs. The noni plant (Morinda citrifolia L) is a herbal plant that can be used as a treatment for various diseases, one of which is cancer. The noni (Morinda citrifolia L) plant contains phytochemicals ranging from fruit, seeds, leaves and roots. This review article aims to examine the cytotoxicity effects of noni (Morinda citrifolia L) plants on cancer cells. The library sources in this article review use the Google Scholar and PubMed databases. The inclusion criteria used were articles containing the cytotoxic test of noni (Morinda citrifolia L) with the last 10 years of publication (2011-2020), original research, there were results of anticancer activity in the form of IC50 and research using noni plant extracts (Morinda citrifolia L). The exclusion criteria used were articles that did not contain a full text, used plants with different genus, did not have an IC50 value and were not original research. From the journals that have been analyzed, it can be said that the extract of the noni (Morinda citrifolia L) plant can be developed for cancer treatment. Noni plant has cytotoxic activity because it contains active compounds in the form of damnacanthal, nordamnacanthal, morindone, flavonoids and alkaloids. Based on the results of the cytotoxic test of Morinda citrifolia extract, the plant parts that have the strongest cytotoxic effect are fruit> roots> root bark> leaves> shoots.